Editorial - Aguirre, Néstor Jaime; Gómez Botero, Maryory Astrid; Orozco-Arroyave, Juan R.; Osorio, Juan Pablo; Villegas, Juan G. (Revista Facultad de Ingeniería Universidad de Antioquia, 2020)
In 2018, the School of Engineering of Universidad de Antioquia (UdeA) celebrated its 75th anniversary. Within this commemoration, the School organized ExpoIngenieria 2018, a broad forum for the interchange of knowledge between Academia, Industry, and the State.